INCREASING STAMPING FORMABILITY OF LOW-CARBON COLD ROLLED THIN STEEL SHEETS - Tatarkina, I.; Doschechkina, I.; Татаркина, И. С.; Дощечкина, И. В.; Татаркіна, І. С.; Дощечкіна, І. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The use of surfactant (épila) was studied as a method for improving the cold-formability of steel sheets. The factors of the resulting effect were analyzed. Application of épila significantly reduc-es the surface roughness and decreases the stress concentrates. Epilam fills pores and microcracks, displaces moisture and gases, thereby reducing metal embrittlement. The application of épila provides the highest category of drawing the low carbon sheet steel 08kp.
ПОВЫШЕНИЕ ШТАМПУЕМОСТИ НИЗКОУГЛЕРОДИСТОЙ ХОЛОДНОКАТАНОЙ ТОНКОЛИСТОВОЙ СТАЛИ
ПІДВИЩЕННЯ ЗДАТНОСТІ ДО ШТАМПУВАННЯ НИЗЬКОВУГЛЕЦЕВОЇ ХОЛОДНОКАТАНОЇ ТОНКОЛИСТОВОЇ СТАЛІ
Keywords: epilam; defects healing; cold rolled sheet; stamping of sheets; stamping formability; drawing; hole-expansion test; drawability; roughness; surface profile; сталь; холоднокатаный лист; технологическая пластичность; штампуемость; вытяжка; испытание на выдавливание; холоднокатаний лист; технологічна пластичність; здатність до штампування; витягування; випробування на видавлювання; 69.017:1539